THE CRIME OF HATE SPEECH THROUGH THE INTERNET (REVIEW OF ARTICLE 28 SECTION (2) OF THE INFORMATION AND ELECTRONIC TRANSACTION LAW) - Nabila Yulianda Inkeputri; Muhammad Rustamaji (Media Keadilan: Jurnal Ilmu Hukum, 2021)
The problems contained in scientific papers are about what are the indicators or limits of hate speech in the ITE Law and how to apply or implement Article 28 of the ITE law on hate speech. This study uses a juridical-normative approach. From this research, it is found that Article 28 of the ITE Law does not explain in detail the indicators of hate speech itself. If grouped, the scope of crime (Hate Speech) is classified as a crime against honor. The next indicator that is included in hate speech is regarding understanding related to hatred and the last one is about elements between groups. In addition to its implementation which opens up space for multiple interpretations and subjectivity, the criminal threats contained in this article which are regulated in Article 45A paragraph (2) of this ITE Law also have problems regarding the application of criminal sanctions in this article are considered to be over the line and not in accordance with the characteristics of the law . this law as an administrative law.